Arsenic in the groundwater of the Upper Brahmaputra floodplain: Variability, health risks and potential impacts. (November 2022) - Goswami, Ritusmita; Neog, Nikita; Bhagat, Chandrashekhar; Hdeib, Rouya; Mahlknecht, Jürgen; Kumar, Manish
Abstract: The upper Brahmaputra floodplain (UBF) is highly enriched with geogenic contaminants, mostly the Arsenic (As), owing to its sensitive geomorphology, aquifer groundwater (GW) dynamics, huge sediment deposition along with natural and anthropogenic disturbance significantly accelerate the As leaching rate into the groundwater, leading to an increase the health risk. Concerning the above active processes in the Lakhimpur district of UBF, current work aims to investigate seasonal dynamics of As contamination and associated health hazard for local community. To carry out this study, 51 GW samples analyzed which reveal the seasonal variation in As concentrations with the minimum average concentration in the monsoon season (4.7 μg.L −1 ) and the maximum in the post-monsoon season (18.5 μg.L −1 ) with 50% of the samples exceeding permissible limits. The differences in the local geological conditions and the GW flow may contribute to the spatial variations in mean As concentration in the study area. Also, the active GW recharge process identified in post-monsoon season accelerates the As leaching in the area's aquifers. Further, results indicate higher As levels associated with a pH range of 6–7 favours As desorption from minerals under reducing conditions. The hazard index indicates that the children population has high carcinogenic risk compared to adult populations. Furthermore, the study highlights the social risk potential arising from public health crises due to As exposure. Overall, results indicate high As concentrations in region with moderate seasonal variability and demand a dire attention for long-term monitoring to provide sustainable water resources to safeguard the people at risk. Graphical abstract: Image 1 Highlights: Effect of upstream/downstream was investigated on As contamination in the groundwater. Four-fold increase in mean arsenic(As) concentration was reported in post-monsoon season. Active groundwater (GW) recharge process was identified in the post-monsoon season. Mainly rock-water interaction mechanism triggers the elevation of As concentration in GW. Children's population was more vulnerable to carcinogenic risk compared to adults.